DEGRADATION DE NITROBENZENE PAR ADSORPTION SUR ARGILE NATURELLE COUPLEE D’UNE OXYDATION PAR LE REACTIF DE FENTON - ELMIR, IMED; BAGUANE, MOHAMED (Courrier du Savoir, 2016)
Nitrobenzene is an important chemical which used in the manufacture of many products such as dyes, plastics, pesticides, explosives, pharmaceuticals products, etc. It is very toxic even present as traces in industrial waste liquids effluents. It may constitute a potential pollution source of faun and flare. It is necessary to investigate technical treatment in aim to reduce the residual concentration of nitrobenzene in environment. In this work the removal of nitrobenzene from synthesized aqueous solutions was carried out by adsorption onto natural clay in presence of Fenton’s reagent at batch processes. The equilibrium was reached at the end of 20 minutes. The adsorption isotherm was well described by the Dubinin-Radushkevich model. The high efficiency of treatment by this technical is 66.51 %, was obtained at the optimum conditions: initial concentration of nitrobenzene (C0 = 246 mg/l), dose of natural clay (DNC = 0.6 g/L), concentration of hydrogen peroxide ([H2O2] = 5μmol/L) and concentration of ferrous ion ([Fe2+] = 50μmol/L).